Human Epidermal Growth Factor Receptor 2 (HER2) as Surrogate Prognostic Marker in Gastric and Gastro Esophageal Junction Cancer - Shareefa Akhter; Nassima Chanda; Rumana Hamid; Malik Tariq Rasool (MRIMS Journal of Health Sciences, 2019)
Background: HER2 is an important biomarker in gastric and gastroesophageal junction tumors. Expression of HER2 status by immunohistochemistry is heterogeneous in various patient populations. This overexpression appears to be an important prognostic factor in gastric cancer and its association with other poor prognostic factors may therefore act as a surrogate marker for poor prognosis in gastric carcinoma. We studied our patient population to look for any such association between HER2 status and various clinicopathological parameters. Objective: To study the association between HER2 status and various clinicopathological parameters. Methods: Patients were prospectively enrolled from August 2013 to March 2015. All relevant patient parameters were recorded. After curative resection, surgical specimens of gastric and gastroesophageal junction adenocarcinoma were analyzed for immunohistochemistry for HER2 by using standard methods. IHC score followed Hofmann's criteria. Statistical analysis of relation between HER2 status and relevant patient and disease characteristics such as gender, age at diagnosis, tumor location, histological type of tumor, stage, and size of tumor, was performed. Results: 106 patients were enrolled into this study. Only 18 (17%) cases had HER2 score of 3+, whereas 5 (4.7%) had equivocal score (2+) and the remaining 84 (78%) tumors tested negative. HER2 status was significantly associated with location of primary tumor, gender, histopathological type of cancer, and size of primary tumor. There was no significant relation between HER2 status and age of patient, depth of invasion, nodal metastasis, or overall stage. Conclusion: Further studies are necessary to determine the significance of HER2 status in upper gastrointestinal cancers especially that the patients need follow up where we can predict the HER2 status as an independent prognostic factor for overall survival.